PREPARATION OF COMPOSITE POLYPYRROLE/1,10-DIBENZYL-1,10-DIAZA-18-CROWN-6 ELECTRODE BY ELECTROPOLYMERIZATION METHOD AS VOLTAMMETRIC SENSOR OF HG2+ ION IN PICOMOLAR CONCENTRATION - Harsini , Muji
Many chemical analyses require analytical methods with low detection limit and high selectivity. Various methods have been developed to decrease the detection limit and to increase the selectivity of chemical analyses. Differential pulse stripping voltammetry is an excellent electroanalytical method for the determination of trace metal ions. This method has high sensitivity due to its preconcentration step on the surface of working electrode. The detection limit of this method can be as low as 10-10 M. A proper choice of the working electrode is crucial for the success of the analyses. The need for lower detection limit and high selectivity of trace metal analysis required modification of electrodes. This normally conducted by incorporating a ligand as ionophore on the surface of the electrode. The used of modified electrode for trace metal analyses can lower the detection limit to 10-11M. The aim of this research is to obtain a new method to modify electrode that can be used to selectively determine Hg2+ ion as low as picomolar (pM) concentration using differential pulse stripping voltammetry method. The need for method having low detection limit on Hg2+ ion are due to high toxicity of mercury. In this research, 1,10-dibenzyl-1,10-diaza-18-crown-6 (DBA218C6) compound will be used as ionophore to make a modified electrode for the determination of Hg2+ using differential pulse stripping. voltammetry method. This was chosen because of its high ability to form complex with Hg2+ ion. This compound is derived from 1,10-diaza-18-crown-6 (A218C6), which is known able to form complex with Hg2+ ion with high stability constant, Kam, = 10 7 9. The A218C6 can also form complex with many other metal ions with lower stability constants. Therefore, modified electrode made using DBA218C6 compound is expected to have low detection limit and high selectivity toward Hg2+ ion. Polypyrrole (PPy) supporting polymer was used to immobilize DBA218C6 compound on the surface of platinum disk electrode. Polypyrrole was chosen because it is conductive polymer and has been used in many applications in surface science and sensors development. Preparation of PPy/DBA218C6 electrode was conducted by electropolymerization of pyrrole on the surface of platinum disk electrode from solution mixture of pyrrole and DBA218C6 using cyclic voltammetry method. Acetonitrile and NaCIO4 were used as solvent and supporting electrolyte, respectively. FTIR spectra of film form on the surface of platinum disk electrode showed that DBA218C6 compound was trapped during electropolymerization of pyrrole to form PPy/DBA218C6 composite. The incorporation of DBA218C6 in polypyrrole backbone was due to its interaction with pyrrole unit during the formation of polypyrrole because the positive charge of every three or four unit pyrrole in poplypyrrole backbone provides electrostatic attraction to free electron pair in DBA218C6 compound. The modified electrode was used as working electrode for determination of Hg2+ ion using differential pulse stripping voltammetry method. Selectivity and detection limit of this electrode in Hg2+ ion analysis was studied. Stripping current depends on accumulation potential, accumulation time, pH of solution, amount of DBA218C6, film thickness, surface area of the electrode, and type of supporting electrolyte used in the measurement. At optimum condition, calibration curve was linier between 0.5 - 5 pM (5.10 13 M - 5.10-12 M) of Hg2+ ion with detection limit of 0,492 pM (4,92.10-1m). The presence of Ag , Cd2+, Cue , and Pb2+ ions at concentration 108 time of Hg2+ ion concentration did not interference the stripping current. Mechanism involves in the analysis of Hg2+ ion on the surface of PPy/DBA2 I 8C6 film consists of chemical and electrochemical reaction. Chemical reactions involve complexation of Hg2+ ion by DBA218C6 to form PPy/(DBA218C6)2-Hg2+ complex. This reaction occurs on the surface of electrode during accumulation process. The accumulation process was conducted at potential of +800 mV vs Ag/AgCI (KCI 3 M) electrode. Electrochemical reaction occurs in stripping process. The stripping process was conducted by scanning working electrode potential from -1000 mV to 0 mV vs Ag/AgC1 (KCI 3 M). At potential lower than -400 mV vs Ag/AgCI (KCI 3 M) the mercury ion in the complex was reduced to Hg and then oxidized back at potential higher than -400 mV vs Ag/AgCl (KCI 3 M) to produce stripping current. This study provide new information and understanding on trapping neutral macrocyclic compound, DBA218C6, in polypyrrole, to form PPy/DBA218C6 film and the use of the film as Hg2+ ion sensor using differential pulse stripping voltammetry method. The results are expected to contribute information on preparing electrochemical sensors in analytical chemistry.